2014
DOI: 10.1016/j.envpol.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of perfluoroalkyl compounds in midge (Chironomus riparius) larvae exposed to sediment

Abstract: Midge larvae (Chironomus riparius) were exposed to sediments from a deposition sampled at a site along the Rhône River (France) downstream of an industrial site releasing various perfluorinated chemicals. This sediment is characterized by high concentrations of perfluoroundecanoic acid (PFUnA) and perfluorotridecanoic acid (PFTrDA) and a low perfluorooctane sulfonate (PFOS) concentration. Concentrations of 23 perfluoroalkyl compounds, including C4-C14 carboxylate acids, C4-C10 sulfonates, and seven precursors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…Extraction of sediment samples was based on the ultrasonic extraction method described by Bertin et al (2014), with some modifications. Sediment samples (1 g dry weight (dw)) were weighed in 15 mL glass tubes.…”
Section: Extraction and Clean-up Of Sediment Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of sediment samples was based on the ultrasonic extraction method described by Bertin et al (2014), with some modifications. Sediment samples (1 g dry weight (dw)) were weighed in 15 mL glass tubes.…”
Section: Extraction and Clean-up Of Sediment Samplesmentioning
confidence: 99%
“…The transfer of PFASs from sediments to aquatic biota is of particular concern, especially for benthic fish or invertebrates that dwell on it (Martin et al, 2004;Bertin et al, 2014). It is therefore essential to document the occurrence and levels of PFASs in sediments, which may subsequently be used to predict the concentration of PFASs in aquatic biota.…”
Section: Introductionmentioning
confidence: 99%
“…For sediment, gammarid samples, leaf samples and the fish tissues used as reference matrix (NIST SRM 1947, Reiner et al, 2012, PFASs were extracted using sonication following the method described in Bertin et al (2014). The OW and PW samples were processed using Strata-X-AW cartridges as described by Labadie and Chevreuil (2011) Replicate procedural blanks were analysed for each series of samples (details in Table S4 in SI).…”
Section: Pfas Extractionmentioning
confidence: 99%
“…Two studies of midge (Chironomus riparius) larvae exposed to field sediment showed rapid accumulation and elimination of two PFCAs (C 11, perfluoroundecanoic acid [PFUnDA] and C 13 acid perfluorotridecanoic [PFTrDA]), PFOS and its perfluorooctane sulfonamide precursor (FOSA) (Bertin et al, 2014;Bertin et al, submitted). Like oligochaetes, chironomid larvae are in direct contact with sediment, and accumulation occurs through food ingestion and diffusion from pore water (PW) through the tegument.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of the suspended particulate matter (SPM) was conducted according to a sediment extraction procedure adapted from Bertin et al [33]. Briefly, filters were sonicated twice with 5 mL of MeOH (20 min).…”
Section: Extraction Proceduresmentioning
confidence: 99%